Automated grade distribution management system of the University of the Philippines in Mindanao - Miro, John Vincent Q. (2005)
The application program focuses on the idea of providing an alternative which may lessen the burden and problems in acquiring and distributing students? true copies of grades. The study resulted in the development of the two components of the system namely, the server-side application program and the Web based client-side application program. The server-side application program gives the administrator the sole authority to supervise the records of students, instructors and courses offered, and to facilitate grade distribution via electronic mail (email). In forwarding copies of grades, the system attaches them to the email messages sent to the destination addresses. The content of these copies may be verified through the client-side application program which provides online access of student grades. Also, it presets venue for the students to register email addresses where their grades will be sent. Making use of this full-featured system, grade distribution process may now be automated, thus, minimizing the difficulties caused by the manual procedure
Thesis (BS Computer Science) -- University of the Philippines Mindanao, 2005